Analysis and comparison of the two sectoring approaches in elevator traffic systems. (September 2019) - Al-Sharif, Lutfi; Hammoudeh, Ahmad; Al-Saidi, Jannat
Sectoring is a group control algorithm that is used in elevator traffic control systems by grouping passengers that have common destinations or common origins into elevator cars that serve these floors. The building is split into sectors usually comprising contiguous floors. Two different alternative algorithms for sectoring are discussed in this paper. The first approach is based on dynamic allocation with equal sector allocation. The second approach is based on static allocation with unequal sector sizes. Under static allocation, the same elevator car is allocated to the same sector in every round trip. Under dynamic allocation, each elevator car is allocated to a different sector in each round trip. Under the dynamic allocation scheme suggested in this paper, the elevator cars are sequenced to the various sectors in the buildings in a round-robin fashion. It is important to note that under both schemes, the provided (relative) handling capacity of different sectors is equalised. Five different buildings have been analysed using the two suggested sectoring algorithms. The building is first designed by finding the required number and speed of elevators assuming conventional control. Each building is then analysed using one of the two suggested sectoring algorithms. In order to compare the performance of the two sectoring algorithms, the provided (relative) handling capacity is calculated. The provided (relative) handling capacity of the two suggested algorithms is then compared. Very little difference was found between the two algorithms. The dynamic sectoring with equal sector sizes offers the convenience of having equal sector sizes. The static sectoring with unequal sector sizes is more convenient for passengers that are familiar with the building. Practical application : This paper analyses two different options for sectoring the control system of an elevator system in a building. Each of the two sectoring methods is suitable for different situations. The dynamic allocation method is more suitable for destination group control systems and offers the group controller more flexibility. The static allocation method with unequal sector sizes ensures that the passengers remain familiar with the elevators that they use to get to their floors. The programmer of the elevator group controller can programme both methods in the controller and allow it to switch to the most suitable algorithm depending on the prevailing conditions.